2013
DOI: 10.1103/physrevb.88.024106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a built-in electric field in asymmetric ferroelectric tunnel junctions

Abstract: The contribution of a built-in electric field to ferroelectric phase transition in asymmetric ferroelectric tunnel junctions is studied using a multiscale thermodynamic model. It is demonstrated in detail that there exists a critical thickness at which an unusual ferroelectric-"polar nonferroelectric" phase transition occurs in asymmetric ferroelectric tunnel junctions. In the "polar nonferroelectric" phase, there is only one nonswitchable polarization which is caused by the competition between the depolarizin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 71 publications
2
40
0
Order By: Relevance
“…However, the existence of built-in field arising from the difference in nature of the top and bottom electrodes in ferroelectric capacitors can lead to asymmetric ferroelectric properties which strongly depend on polarization direction. 13 As shown in Fig. 2, the electrocaloric temperature changes under adiabatic application of an electric field for the two opposite polarization (i.e., ON and OFF states) orientations can be different, 14 just like the tunnel electroresistance effect in ferroelectric tunnel junctions.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existence of built-in field arising from the difference in nature of the top and bottom electrodes in ferroelectric capacitors can lead to asymmetric ferroelectric properties which strongly depend on polarization direction. 13 As shown in Fig. 2, the electrocaloric temperature changes under adiabatic application of an electric field for the two opposite polarization (i.e., ON and OFF states) orientations can be different, 14 just like the tunnel electroresistance effect in ferroelectric tunnel junctions.…”
Section: 3mentioning
confidence: 99%
“…2 In addition to the use of first-order transition materials, other strategies to enhance the caloric properties are possible such as geometrical optimization, [10][11][12][13][14] maximizing the number of close-energy phases near a critical point in the temperature-composition phase diagram, [15][16][17] combining conventional and inverse caloric responses in a single refrigeration cycle, 18,19 introducing extra available degree of freedom like strain via mechanical stress, [20][21][22] and multicaloric effect driven by either single stimulus or multiple stimuli (applied/removed simultaneously or sequentially). 5 There are several excellent review articles and books treating on the electrocaloric effect through its history, related properties, and potential design for cooling applications.…”
Section: 3mentioning
confidence: 99%
“…[36][37][38][39] In particular, the electrocaloric properties of BTO thin films have been intensively investigated. 12,18,19,26,[40][41][42][43][44][45][46][47] Interestingly, it was reported that applying a uniaxial compressive stress could enhance and widen the electrocaloric response considerably in ultrathin BTO films due to tuning of the depolarization field. 26 It is also reported that the electrocaloric peak under tensile stresses moves towards higher temperatures with its magnitude slightly enhanced in BTO single crystals.…”
mentioning
confidence: 99%
“…This would be in agreement with an increase in the built-in electric field E bi = (Φ 2 − Φ 1 )/t × e with the TE work function. 33,34 As this electric field favors the downward polarization state, the application of larger electric fields is required to switch the polarization toward the TE when E bi increases.…”
mentioning
confidence: 99%